Sintesis Biodiesel Dari Minyak Nyamplung (Calophyllum Inophyllum) Menggunakan Katalis Heterogen Nh4-Geopolimer - Ganis Kharisma Wiranti; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Biodiesel is an alternative energy to replace fossil fuels that have the advantage of producing less gas emissions and higher combustion efficiency. Biodiesel is produced by transesterification reaction of vegetable oil. During the process of making biodiesel usually used NaOH or KOH as homogeneous catalyst which has the disadvantage of formation side products such as soaps and complexity of the separation of catalyst because having the same phase. Therefore, in this study biodiesel was synthesized from calophyllum inophyllum oil using geopolymer catalyst. Geopolymer was synthesized by mixing sodium silicate, metakaolin, sodium hydroxide, aquadest, and ammonium nitrate. The process variables are weight of oil 50 grams, stirring rate 400 rpm, reaction time 120 minutes, and temperature of 65 oC, with catalyst 3% (w/w) and mole ratio of methanol:oil 1:12. The yield of biodiesel 94,14% with density 881,17 kg/m3, kinematic viscosity 3,66 mm2/s, the acid number of 0,25 mg-KOH/g biodiesel, and the flash point 146°C respectively accordance with the standards of Indonesian biodiesel (SNI 7182:2015). Keywords: biodiesel, callophyllum inophyllum oil, geopolymer, transesterification, yield